An exceptional cause of hemoptysis in the elderly patient : IgA vasculitis. Issue 4 (4th July 2018) - Pourcelet, Aline; Georgery, Marine; Vandergheynst, Frederic; Hougardy, Jean-Michel; De Breucker, Sandra
ABSTRACT: We describe here the case of a 73-year-old woman who presented a recurrent macular rash, acute respiratory distress, and hemoptysis. Chest CT scan showed diffuse ground-glass opacities that were suggestive of alveolar hemorrhage. With the development of severe acute kidney injury and nephrotic-range proteinuria (creatininemia 2.6 from 1.9 mg/dL with overt proteinuria 34 from 2.1 g/g creat), a kidney-lung syndrome was evoked. Skin biopsy revealed leukocytoclastic vasculitis with IgA deposits. Blood tests showed an increased IgA level. Those findings were consistent with a rare form of IgA vasculitis (formerly Henoch-Schönlein syndrome), the originality of the case lying in the occurrence of a kidney-lung syndrome in an elderly patient.